Analysis Of Factors Influencing Mother's Interest Towards Long Term FP Methods In Sukatani Village, District Karawang In 2023 - Tsuay Batul Islamiyah; Wiwin Widyastuti; Nur Sitiyaroh; Nur Anita; Olivia Nency (Journal of Innovative and Creativity, 2025)
Family Planning (KB) is one way to reduce the number of children towards a happy and prosperous family. Long-Term Contraceptive Method (LTM) is a contraceptive that can be used for a long period of time, more than two years, effective and efficient for the purpose of spacing births for more than three years or ending pregnancy in couples who no longer want to have more children. To determine the analysis of factors that influence mothers' interest in long-term family planning methods in Sukatani Village, Karawang Regency in 2023. The type of research used in this study is analytical with a cross-sectional design. The population in this study were mothers aged 35-49 years as many as 115 respondents, the technique used was accidental sampling. The sample in this study was 90 people. Bivariate analysis using the chi-square test. respondents had low interest in using long-term birth control methods, as many as 50 people (64.4%), most respondents had less knowledge about long-term birth control methods, as many as 48 people (53.3%), most respondents received support from their husbands, but did not support long-term birth control methods, as many as 52 people (57.8%). It can be concluded that there is a significant relationship between husband's knowledge and support and mothers' interest in long-term family planning methods in Sukatani Village, Karawang Regency in 2023.